Measuring in-hospital quality multidimensionally by integrating patients’, kin’s and healthcare professionals’ perspectives: development and validation of the FlaQuM-Quickscan - Claessens, Fien; Seys, Deborah; Van der Auwera, Charlotte; Jans, Anneke; Castro, Eva Marie; Jacobs, Laura; De Ridder, Dirk; Bruyneel, Luk; Leenaerts, Zita; Van Wilder, Astrid; Brouwers, Jonas; Lachman, Peter; et al. (BMC health services research, 2023)
Background Measuring quality is essential to drive improvement initiatives in hospitals. An instrument that measures healthcare quality multidimensionally and integrates patients’, kin’s and professionals’ perspectives is lacking. We aimed to develop and validate an instrument to measure healthcare quality multidimensionally from a multistakeholder perspective. Methods A multi-method approach started by establishing content and face validity, followed by a multi-centre study in 17 Flemish (Belgian) hospitals to assess construct validity through confirmatory factor analysis, criterion validity through determining Pearson’s correlations and reliability through Cronbach’s alpha measurement. The instrument FlaQuM-Quickscan measures ‘Healthcare quality for patients and kin’ (part 1) and ‘Healthcare quality for professionals’ (part 2). This bipartite instrument mirrors 15 quality items and 3 general items (the overall quality score, recommendation score and intention-to-stay score). A process evaluation was organised to identify effective strategies in instrument distribution by conducting semi-structured interviews with quality managers. Results By involving experts in the development of quality items and through pilot testing by a multi-stakeholder group, the content and face validity of instrument items was ensured. In total, 13,615 respondents (5,891 Patients/kin and 7,724 Professionals) completed the FlaQuM-Quickscan. Confirmatory factor analyses showed good to very good fit and correlations supported the associations between the quality items and general items for both instrument parts. Cronbach’s alphas supported the internal consistency. The process evaluation revealed that supportive technical structures and approaching respondents individually were effective strategies to distribute the instrument. Conclusions The FlaQuM-Quickscan is a valid instrument to measure healthcare quality experiences multidimensionally from an integrated multistakeholder perspective. This new instrument offers unique and detailed data to design sustainable quality management systems in hospitals. Based on these data, hospital management and policymakers can set quality priorities for patients’, kin’s and professionals’ care. Future research should investigate the transferability to other healthcare systems and examine between-stakeholders and between-hospitals variation.